Upaya Peningkatan Pendapatan Petani Sayuran dengan Konsep Circle Business Sampah Organik Pada Kelompok Tani Sidodadi Lestari Paal Lima Kota Jambi - Khalik, Idham; Syarif, Agus; Nur Budi Utama, Ahmad; Armando, Y.G; Setyaji, Hajar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Sidodadi Lestari farmer group is a vegetable farmer group located in Paal Merah Jambi City whose area is directly adjacent to Jambi Sultan Thaha Airport, which means that the area is an area that is maintained as an airport peripheral area. As an agricultural area for vegetable commodities, the Sidodadi Lestari farmer group tries to cultivate its land with vegetable crops that are in demand by people in Jambi city, such as kale, spinach, slada, long beans, chili, and plants. The Sidodadi farmer group currently still uses chemical fertilizers mixed with commercially purchased manure. The group is appropriate as a model for the development of the circle business concept of organic waste to minimize waste and is expected to increase the income of the farmer group. The purpose of community service to the Sidodadi farmer group is to introduce the concept of Circle bussines organic waste through liquid fertilizer production technology in vegetable cultivation in the Sidodadi Lestari farmer group. The service method uses the method of socialization of activities, demonstration of making liquid organic fertilizer and practice by farmer groups. The implementation of the activity went according to plan, the Sidodadi Lestari farmer group was able to apply the Circle bussines concept of organic waste in their vegetable-based farming activities. The Sidodadi Lestari farmer group has the potential to increase income income by Rp.500,000 a month, and if the production capacity is increased, the potential income income will be greater.